2021
DOI: 10.1021/acs.jpcc.1c03733
|View full text |Cite
|
Sign up to set email alerts
|

Solid State Photon Up-Conversion Emission from Chromophore-Tethered PPV Films

Abstract: Solid state triplet–triplet annihilation (TTA) upconversion (UC) systems may find application as elements in a wide range of practical photon energy conversion technologies. One strategy to produce highly efficient UC emission in the solid state is to create systems that can efficiently transport generated triplets to distances significantly longer than afforded by the Dexter mechanism under restriction of molecular movement. In this work, we present a new solid state UC system through integration of conjugate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 65 publications
(101 reference statements)
0
8
0
Order By: Relevance
“…Mori et al have also investigated PPV derivatives by conjugating an additional chromophore unit, the 9,10-bisphenylethynylanthracene (BPEA) as an annihilator, and used palladium( ii ) meso -tetraphenyltetrabenzoporphyrine (TBP) as a sensitizer. 77 Their results suggest that the covalently bound BPEA units increase the TET rate in comparison with pure PPV, while also being a source of energy loss due to energy back transfer at a high BPEA ratio.…”
Section: Progress and Challengesmentioning
confidence: 99%
“…Mori et al have also investigated PPV derivatives by conjugating an additional chromophore unit, the 9,10-bisphenylethynylanthracene (BPEA) as an annihilator, and used palladium( ii ) meso -tetraphenyltetrabenzoporphyrine (TBP) as a sensitizer. 77 Their results suggest that the covalently bound BPEA units increase the TET rate in comparison with pure PPV, while also being a source of energy loss due to energy back transfer at a high BPEA ratio.…”
Section: Progress and Challengesmentioning
confidence: 99%
“…32 Using polystyrene derivatives (PPV) as the polymer matrix and the selection of PdTBP as the photosensitizer molecule, BPEA as the acceptor molecule was reported by Nattestad's group in 2021. 37 The authors used a copolymerization method to link the photosensitizer and acceptor molecules on a polystyrene molecule, with the polymer serving as the exciton transfer medium. It was found that the introduction of a small ratio ( ca.…”
Section: Tta-uc In Polymer Films Doped With Uc Componentsmentioning
confidence: 99%
“…[6][7][8][9][10][11][12][13] Owing to their easily executable and inexpensive processing protocols, solution processable TTA-UC solid-state mixtures prepared by using small molecular and macromolecular p-conjugated systems are ideal candidate systems to be used as TTA-UC interlayers for device applications. [14][15][16] The solution processable character of TTA-UC organic materials offers an attractive opportunity to complement the portfolio of other existing photon energy up-converting systems [17][18][19][20][21] and to avoid disruptions in the design of currently employed device architectures. Although the realization of TTA-UC layers as functional device components is lagging, encouraging results were recently presented on a green-to-blue model TTA-UC composite prepared by blending the greenabsorbing (2,3,7,8,12,13,17,18-octaethyl-porphyrinato) Pt II (PtOEP) square-planar sensitizer with the blue-light emitting 9,10 diphenyl anthracene (DPA) emitter, a polycyclic aromatic hydrocarbon derivative.…”
Section: Introductionmentioning
confidence: 99%